Design, pharmacophore based screening, docking and molecular simulation study of some novel pyrazine derivatives against Mycobacterium tuberculosis Fatty Acid Synthase I - AKHILESH KUMAR BILAIYA; DR GAJANAND ENGLA (The Bioscan, 2025)
This manuscript elucidates the conceptualization and computational assessment of innovative pyrazine derivatives. A pharmacophore-based screening approach was done toward the identification of lead compounds based on a developed pharmacophore model encapsulating critical structural features for the inhibition of FAS.274pyrazine derivative of seven series S1, S2, S3, S4, S5, S4, and S7weredesigned and screened for drug likeness.273 passed drug likeness filter were screened using high-throughput virtual screening to filter candidates with an optimal pharmacophore fit score. Molecular docking studies were then carried out on 16 selected compounds (S1-20, S1-31, S2-14, S2-18, S3-22, S4-21, S6-21, S6-13, S6-18, S6-24, S6-25, S6-28, S7-19, S7-2, S7-17, and S7-26) against the active site ofMycobacterium tuberculosis Fatty Acid Synthase I(FAS I) . Molecular dynamics simulations were then performed with the S6-25. An integrated computational approach here identified S6-25 having good potential as inhibitors of FASI.